Absence of hemoglobin increase is associated with reduced graft survival after kidney transplantation. Issue 5 (31st January 2022) - Goldman, Shira; Schechter, Amir; Steinmetz, Tali; Agur, Timna; Shepshelovich, Daniel; Gafter‐Gvili, Anat; Hanniel, Iddo; Rozen‐Zvi, Benaya; Rahamimov, Ruth
Abstract: Background: Anemia is prevalent following kidney transplantation and is associated with reduced graft survival. The association between temporal changes in hemoglobin (Hb) level at the early post‐transplant period and graft survival is unknown. Patients and methods: The study cohort included consecutive patients included in a single center transplantation registry between January 2002 and December 2016. Temporal changes in Hb values during the first 90 days after the transplantation were evaluated by piecewise linear regression model. Significant Hb increase rate was defined as an increase of .5 gram/deciliter/month. Patients were divided into groups according to the presence of significant Hb increase. The primary outcome was death‐censored graft failure. Results: Of 946 patients included in the study cohort, 831 (87.8%) had at least one interval of Hb increase, and 115 (12.2%) had no Hb increase. The absence of Hb increase was associated with an elevated risk of death censored graft failure by univariate (HR 2.9, 95% CI 1.88–4.49, P < .001) and multivariate (HR 2.47, 95% CI 1.48–4.12, P = .001) analyses. The timing and rate of Hb increase had no association with the main outcome. Conclusions: Lack of Hb increase during the early post‐transplant period is associated with an increased risk of graft loss.